Pengaruh UU Anti-Monopoli (UU No. 5/1999) terhadap Pembangunan Ekonomi di Indonesia - Saputra, Adit (Badan Riset dan Inovasi Daerah Sulawesi Tengah, 2025)
Law plays a crucial role in promoting economic development in Indonesia. As a social instrument, law functions not only to regulate behavior but also as a means of social and economic engineering aimed at improving public welfare. One concrete manifestation of the law’s influence on economic development is the enactment of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, which serves as the legal foundation for creating a healthy and competitive business climate. This law aims to protect public interests, enhance national economic efficiency, and ensure fair business opportunities for all types of entrepreneurs. Through this regulation, the law balances the interests of business actors and the public, prevents market domination by certain groups, and promotes equitable economic distribution. The establishment of the Business Competition Supervisory Commission (KPPU) as an independent institution strengthens the enforcement of fair competition. Thus, effective implementation of economic law contributes to sustainable, just, and constitutionally grounded economic growth in accordance with the values of Pancasila and the 1945 Constitution.